Experimental and Density Functional Theory Calculations Study on 2,3-Di(p-methylphenyl)tetrazole-5-thione - ZHAO, P.S.; JIAN, F.F.; ZHUANG, R.R.; ZHENG, J. (Asian Journal of Chemistry, 2010)
2,3-Di(p-methylphenyl)tetrazole-5-thione has been synthesized and characterized by elemental analysis, FTIR, electronic absorption spectra and X-ray single crystal diffraction. Density functional theory method calculations at B3LYP/6-31G* level of the structure, atomic charges distribution, vibration frequencies and the thermodynamic properties at different temperatures have been performed and the results show that the exocyclic sulfur atom has the biggest negative charge values and this site is the most likely site of protonation and methylation as well as the potential coordination site with metallic ions. The calculation of the second order optical nonlinearity has been carried out, and the molecular hyperpolarizability is 13.994 × 10-30 esu, indicating that 2,3-di(p methylphenyl) tetrazole-5-thione is a good candidate as secondorder nonlinear optical material.